Why patients delay or decline treatment for gingival recession: a qualitative study - Omid Fakheran; Erfan Davari Dolatabadi; Sajede Sheydaei; Majid Shahmoradi (BMC Oral Health, 2026)
Abstract Background Gingival recession is a common mucogingival condition associated with esthetic concerns, dentin hypersensitivity, and root-surface complications that may impair oral health-related quality of life. Nevertheless, some patients delay or decline treatment despite being aware of the condition. This study explored patient-perceived barriers to seeking treatment for gingival recession. Methods Semi-structured, face-to-face interviews were conducted with 15 participants who were aware of their gingival recession and were recruited from dental clinics through purposive sampling to achieve maximum variation. Interviews lasted approximately 30–45 min, were audio-recorded with participants’ consent, and explored their experiences and reasons for delaying or declining treatment. Data were analyzed using inductive qualitative content analysis. Trustworthiness was supported through established procedures addressing credibility, dependability, transferability, and confirmability. Results Two overarching themes were identified: Internal Patient-Level Barriers and External Structural Barriers. Internal barriers encompassed treatment-related fear and procedural anxiety, previous negative dental experiences, uncertainty about the necessity or appropriateness of treatment recommendations, low perceived urgency, and concerns about treatment outcomes. External barriers involved information and misconceptions, financial constraints and family support, and access to periodontal care. Three concerns appeared particularly salient to gingival recession treatment: anxiety about grafting procedures and palatal donor-site harvesting, low perceived urgency when symptoms were mild, and uncertainty about the long-term stability of treatment outcomes. Conclusions Barriers to treatment for gingival recession extend beyond those commonly reported in general dental care and include concerns specific to periodontal plastic surgery. Clear communication about procedural morbidity, expected benefits and limitations, and the long-term stability of treatment outcomes, together with improved access to periodontal care, may support informed and preference-sensitive treatment decisions.